Teatro en el Perú de la Post-Pandemia:: Tecnovivio, la nueva “normalidad” y una reflexión sobre lo que el confinamiento nos hizo recordar - Holguín Girón, Francisco Antonio Víctor (2023)
This essay is a reflection on the role of communication technologies in theater during the post-pandemic period, and on the commitments that must be re-assumed as artists, teachers and students of performing arts in the Peruvian context. Taking the premise that theater requires the physical presence of actors and spectators to exist and, in turn, that the intervention of digital media is an unstoppable constant in the social evolution, we conclude on the need to involve technologies and the Internet as part of the process of poetic-scenic construction, as well as the importance of redoubling the effort to generate spaces for the physical encounter between artists and spectators.